Upaya Kejaksaan Negeri Tanah Datar Dalam Mengembalikan Kerugian Negara Berupa Pembayaran Uang Pengganti - Amelia, Yusra; Sukmareni, Sukmareni; Munandar, Syaiful (Faculty of Law, Diponegoro University, 2023)
The purpose of this research is to understand, know and analyze efforts, obstacles faced and how to overcome obstacles in the way of returning state losses in the form of reimbursement payments based on Decision Number: 42/Pid.Sus-TPK/2022/PN Pdg. The research method used is by using empirical juridical methods. explained that the amount of compensation money is not only the amount of state losses incurred but the amount of property obtained or enjoyed from criminal acts of corruption. In essence, in payment of replacement money there are three stages, namely the stage investigation, prosecution and after the issuance of a decision. If the convict does not pay off the replacement money, there will be an additional penalty in the form of imprisonment.